Uso de problemas del canguro matemático en la enseñanza de la geometría en los estudiantes de grado octavo (2018)
This research looks for improving the mathematical reasoning skills in eighth grade students specifically in geometry. The problem solving is an important aspect in the cognitive development, however it is an issue that avoids inside the classroom because of the teachers don’t want to teach mathematics by means of problems, this process allows the acquisition of new knowledge. In the mathematical learning process is essential that the student can work with problems in order to catch their interest, creativity, creating methods or strategies to solve and doing conjectures in a space where the dialogue, contributions and interventions have influence in the learning process.